Ultrafiltration in Decompensated Heart Failure with Cardiorenal Syndrome - Bart, Bradley A; Goldsmith, Steven R; Lee, Kerry L; Givertz, Michael M; O'Connor, Christopher M; Bull, David A; Redfield, Margaret M; Deswal, Anita; Rouleau, Jean L; LeWinter, Martin M; Ofili, Elizabeth O; Stevenson, Lynne W; et al. (The New England journal of medicine, 2012)
Patients with decompensated heart failure and cardiorenal syndrome were randomly assigned to ultrafiltration or diuretic therapy. Ultrafiltration was inferior to diuretics with respect to the primary end point, a bivariate measure of change in creatinine and body weight. The acute cardiorenal syndrome (type 1) is defined as worsening renal function in patients with acute decompensated heart failure. 1 It occurs in 25 to 33% of patients with acute decompensated heart failure and is associated with poor outcomes. 1 , 2 Multiple processes contribute to the development of the acute cardiorenal syndrome, including extrarenal hemodynamic changes, neurohormonal activation, intrarenal microvascular and cellular dysregulation, and oxidative stress. 1 In some cases, intravenous diuretics, which are often administered in patients with acute decompensated heart failure, 3 may directly contribute to worsening renal function. 1 , 4 , 5 The use of diuretics to treat persistent congestion after the onset . . .